2009
DOI: 10.1177/0363546509333011
|View full text |Cite
|
Sign up to set email alerts
|

An Autologous Cartilage Tissue Implant NeoCart for Treatment of Grade III Chondral Injury to the Distal Femur

Abstract: Pain was significantly reduced 12 and 24 months after NeoCart treatment. Trends toward improved function and motion were observed 24 months after implantation. The MRI indicated implant stability and peripheral integration, defect fill without overgrowth, progressive maturation, and more organized cartilage formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 40 publications
1
105
0
Order By: Relevance
“…There has long been an evolution in the use of biomaterials for implantation techniques. [1][2][3][4][5][6][7][8][9][10] Theoretically, it is the best to engineer artificial cartilage that is similar to normal cartilage in physicochemical properties. A couple of products are now under clinical trials to get into the market.…”
Section: Introductionmentioning
confidence: 99%
“…There has long been an evolution in the use of biomaterials for implantation techniques. [1][2][3][4][5][6][7][8][9][10] Theoretically, it is the best to engineer artificial cartilage that is similar to normal cartilage in physicochemical properties. A couple of products are now under clinical trials to get into the market.…”
Section: Introductionmentioning
confidence: 99%
“…Crawford et al 52,75 described a novel technique using tissue-engineered bovine type I collagen scaffold seeded with autologous chondrocytes, which were preconditioned in a bioreactor including the application of hydrostatic pressure prior to implantation. In clinical trials, the authors saw advantages for treatment of medium-and large-sized chondral lesions after 2 years, with respect to the IKDC, KOOS, and Short Form-36.…”
Section: Developments In Acimentioning
confidence: 99%
“…Intense clinical research continues, as new indications for collagen-based scaffold technologies are sought and long-term clinical outcomes are reevaluated. In a recent study, Crawford et al studied the safety and healing potential of commercial cartilage matrix seeded with autologous chondrocytes (NeoCart) in the human knee (Crawford et al, 2009). The study revealed significantly reduced pain in the treatment group, with neocartilage formation that was well integrated.…”
Section: Collagenmentioning
confidence: 99%